2012
DOI: 10.1039/c2dt30076a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular “light switch” for G-quadruplex DNA: cycling the switch on and off

Abstract: We report a new G-quadruplex DNA "light switch", where the light switch can be cycled on and off through the successive introduction of G-quadruplex DNA and [Fe(CN)(6)](4-) ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…It has been previously shown that G-quadruplexb inders can stack on the surface of both terminal G-quartet planes. [10][11][12][13][14][15] Both complexes 1 and 2 contain asquare p-aromatic surface, the dppzi ligand preferred to stacki nt he center of at erminal G-quartet end. For the antiparallel basket G-quadruplex structure, both the diagonal and the parallel loop bindingp ositions were considered.…”
Section: Calculation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that G-quadruplexb inders can stack on the surface of both terminal G-quartet planes. [10][11][12][13][14][15] Both complexes 1 and 2 contain asquare p-aromatic surface, the dppzi ligand preferred to stacki nt he center of at erminal G-quartet end. For the antiparallel basket G-quadruplex structure, both the diagonal and the parallel loop bindingp ositions were considered.…”
Section: Calculation Studiesmentioning
confidence: 99%
“…Recently, our laboratory found that [Ru(L) 2 (dppz)] 2+ (L=2,2′‐bipyridine or 1,10‐phenanthroline) can serve as a prominent molecular “light switch” for both G‐quadruplexes and the i‐motif, which prefers binding G‐quadruplexes over the i‐motif 12. Furthermore, we reported the first example of a reversible G‐quadruplex DNA “light switch”, the switch can be cycled through the competition of [Fe(CN) 6 ] 4− ions and G‐quadruplex DNA 13. We also discovered that the conformation of G‐quadruplex DNA can be regulated by adjusting the pH value in the acidic region, thereby accounting for the on‐off‐on “light‐switch” effect 14.…”
Section: Introductionmentioning
confidence: 98%
“…Ruthenium(II) complexes have been reported to be G‐quadruplex stabilisers2125 and probes 2629. Ruthenium(II) complexes, especially dinuclear ruthenium(II) complexes, offer substantial advantages over organic compounds,3035 other metal complexes (Pt, Ni, etc.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 We have modified the main ligand of [Ru(phen) 2 dppz] 2+ (1) and obtained two similar structured complexes, however, their luminescence properties underwent tremendous changes. For instance, by attaching an imidazole ring to the dppz ligand, complex 2 had an enlarged the π-extended planar, but in the presence of DNA or in aprotic solvent, its luminescence intensity had no significantly growth compared to [Ru(phen) 2 dppz] 2+ (1).…”
Section: Introductionmentioning
confidence: 99%